Prospective Elective Neurosurgical Theater Utilization Audit in Pakistan: Problems in a Public Tertiary Care Hospital and Proposed Solutions from Lower-Middle-Income Country - Ashraf, Mohammad; Kamboh, Usman Ahmad; Raza, Muhammad Asif; Khan, Muhammad Irfan; Sultan, Kashif Ali; Choudhary, Nabeel; Hussain, Syed Shahzad; Ashraf, Naveed (Asian Journal of Neurosurgery, 2022)
Background In lower-middle-income countries such as Pakistan, public hospitals provide free healthcare but suffer from poor management and misgovernance, negatively impacting service provision. One aspect of this is operating theater time (OTT) utilization. In a 1,600-bed hospital with a 22 million catchment population, we noticed significant delays and inadequate OTT efficiency at the neurosurgery department of Jinnah Hospital, Lahore, Punjab, Pakistan. This audit aimed to analyze the neurosurgical OTT utilization, identify delays, and highlight managerial deficiencies and areas for improvement while comparing our workflow with contemporary international literature.Materials and Methods We prospectively audited OTT utilization at the neurosurgical department. All elective surgeries from January to April 2021 were included to identify delays concerning patient transfer, anesthesia team arrival, preparation and intubation time, operative time, and anesthesia extubation time.Results Fifty-six per cent of OTT was utilized operating. Sources of delay included the delayed arrival of anesthesia team (4.7%) and the delay in transferring patients to OT (9.7%). Anesthesia intubation and preparation time accounted for 23% of OT utilization and was significantly longer than the comparable international studies. Extubation time accounted for 5.7% of OT utilization. The issues surrounding transfer delays and prolonged anesthesia time were discussed, with strategies to address them developed with close vital input from our anesthesia colleagues and ward staff.Conclusion Gross delays relatively simple in nature were identified due to poor management and less than ideal interspecialty coordination. Most delays were avoidable and can be addressed by proper planning, optimization of patient transfer and resources, and, most importantly, improved communication between surgeons, anesthetists, and ward staff. This can ensure optimal use of theater time and benefit all specialties, including ancillary staff, and, most importantly, the patient. A reaudit is warranted to assess the impact of interventions on OTT utilization.
Keywords: audit; neurosurgery; operating time; theatre utilization; Pakistan; neuroanaesthesia